Studies on the Culture Condition of Pangus (Pangasius hypophthalmus) at Different Farms in Trishal Upazila - Hossain, MI; Shikha, FH; Chakrabarty, T (Journal of Environmental Science and Natural Resources, 2019)
The present study was conducted to investigate existing culture conditions of pangus (Pangasius hypophthalmus) at farms in Trishal Upazila under Mymensingh district during January to June, 2016. Data were collected with questionnaire by personal interviewing of the respondents. The study result showed that- the farmers of large category are about 60% where 47% farmers have leased pond. Most of the farmer use deep tube-well water as source, 87% farmers practice monoculture of pangus and monitored the health of fish in a regular basis. Only 13% farmer reported diseases occurred in their pond. Most of the pangus farmers used homemade or local farm made supplementary feeds for pangus culture. The study showed that development of better farming system, improving water management, stocking of quality fingerlings, health monitoring and use of prime and standard quality feed has resulted better pangus production in Trishal area. J. Environ. Sci. & Natural Resources, 11(1-2): 97-107 2018